Probing cosmic dawn: modelling the assembly history, SEDs, and dust content of selected z ∼ 9 galaxies. Issue 3 (25th January 2019) - Katz, Harley; Laporte, Nicolas; Ellis, Richard S; Devriendt, Julien; Slyz, Adrianne
ABSTRACT: The presence of spectroscopically confirmed Balmer breaks in galaxy spectral energy distributions (SEDs) at $z$ > 9 provides one of the best probes of the assembly history of the first generations of stars in our Universe. Recent observations of the gravitationally lensed source, MACS 1149_JD1 (JD1), indicate that significant amounts of star formation likely occurred at redshifts as high as $z$ ≃ 15. The inferred stellar mass, dust mass, and assembly history of JD1, or any other galaxy at these redshifts that exhibits a strong Balmer break, can provide a strong test of our best theoretical models from high-resolution cosmological simulations. In this work, we present the results from a cosmological radiation hydrodynamics simulation of the region surrounding a massive Lyman-break galaxy. For two of our most massive systems, we show that dust preferentially resides in the vicinity of the young stars thereby increasing the strength of the measured Balmer break such that the simulated SEDs are consistent with the photometry of JD1 and two other $z$ > 9 systems (GN-z10-3 and GN-z9-1) that have proposed Balmer breaks at high redshift. We find strong variations in the shape and luminosity of the SEDs of galaxies with nearly identical stellar and halo masses, indicating the importance of morphology, assembly history, and dust distribution in making inferences on the properties of individual galaxies at high redshifts. Our results stress the importance that dust may play in modulating the observable properties of galaxies, even at the extreme redshifts of $z$ > 9.